2019
DOI: 10.48550/arxiv.1902.08646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OpenKiwi: An Open Source Framework for Quality Estimation

Abstract: We introduce OpenKiwi, a PyTorch-based open source framework for translation quality estimation. OpenKiwi supports training and testing of word-level and sentence-level quality estimation systems, implementing the winning systems of the WMT 2015-18 quality estimation campaigns. We benchmark OpenKiwi on two datasets from WMT 2018 (English-German SMT and NMT), yielding state-of-the-art performance on the word-level tasks and near state-of-the-art in the sentencelevel tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Next, we experimented on the effect of predictors pretrained with different language pairs by using the trained predictor weights provided along with the WMT20 shared task and OpenKiwi (Kepler et al, 2019b). We utilized the weight except for the embedding layers.…”
Section: Results Of Fine-tuning Pretrained Predictormentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we experimented on the effect of predictors pretrained with different language pairs by using the trained predictor weights provided along with the WMT20 shared task and OpenKiwi (Kepler et al, 2019b). We utilized the weight except for the embedding layers.…”
Section: Results Of Fine-tuning Pretrained Predictormentioning
confidence: 99%
“…We adapts "OpenKiwi" (Kepler et al, 2019b), an open-source framework for QE task, to construct our proposed ensemble-based QE model in Figure 1. Similar as other state-of-the-art methods (Kim et al, 2017;Wang et al, 2018), we use a neural-based architecture, which is mainly based on the predictor-estimator architecture initially proposed from (Kim et al, 2017).…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of embedding-based metrics has proven to achieve the highest performance in recent WMT shared tasks for quality metrics (e.g. [7,8,12]). We take BERTScore as representative of this category.…”
Section: Related Workmentioning
confidence: 99%
“…Good evaluation metrics should have a high correlation with human judgement on the quality of translation. Recently some automatic metrics have achieved a significant correlation with human judgement on the WMT Metrics task datasets (see [7,8,12]). However, research has reported weaker correlation with low human assessment score ranges for segment-level evaluation [20,19].…”
Section: Introductionmentioning
confidence: 99%